Between Freedom and Equality: L. T. Hobhouse and the Idea of Social-Liberal Concept of Education - Bartłomiej Kossakowski-Kisiel (Paedagogia Christiana, 2023)
The idea of education has evolved through debates on the different visions of the goals to be served by the education of citizens. One of the objectives of education concerns the individual’s role as a member of society, wherein individual and collective values are juxtaposed; this objective is linked to the centuries-old debate between liberal and conservative views on how society should be. In this paper, the attempt is to reconstruct the socio-philosophical thought of Leonard Trelawny Hobhouse, one of the main representatives of the New Liberals among British intellectuals at the turn of the 20th century. His thinking can be considered an alternative approach to the relationship between the individual and the state. Although the question of education does not appear to be the main focus of the philosopher’s writings, it seems, however, that the framework of the concept of education can be set by drawing on his anthropological, axiological and normative theory. The specific value of Hobhouse’s thought should be seen not only in the context of the crisis of contemporary liberal thought but also as an attempt to discuss the education founded on philosophy, rather than ideology. The thinker uniquely combines freedom, the central idea of liberalism, with the idea of equality. In this new perspective of society, the individual, while pursuing the concept of good for self, does not lose sight of the other members of society.